DHA for Optimal Health - Barbara Meyer (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This Special Issue of Nutrients, entitled "DHA for Optimal Health", consists of evidence-based original research or reviews of the scientific literature. Manuscripts focus on the evidence that underpins dietary requirements throughout the lifespan (from in-utero to the elderly) for optimal brain function and/or prevention (or treatment) of disease.